The complex interplay between ERK1/2, TGFβ/Smad, and Jagged/Notch signaling pathways in the regulation of epithelial-mesenchymal transition in retinal pigment epithelium cells. - Xiaoyun Chen; Wei Xiao; Wencong Wang; Lixia Luo; Shaobi Ye; Yizhi Liu (PLoS ONE, 2014)
Epithelial-mesenchymal transition (EMT) of retinal pigment epithelium (RPE) cells is a major pathologic change in the development of proliferative vitreoretinopathy (PVR), which leads to severe visual impairment. ERK1/2 pathway has been reported to play a key role in the carcinogenesis, cancer metastasis, and multiple fibrotic diseases. We hypothesized that ERK1/2 signaling could cross-interact with transforming growth factor β2 (TGFβ2)/Smad and Notch signaling pathways in the regulation of EMT in RPE cells. Here, we demonstrated that ERK1/2 signaling was activated in TGFβ2-induced EMT in human RPE cells, while blockade of the canonical TGFβ2/Smad2/3 signaling with SB431542 could not inhibit TGFβ2-induced the activation of ERK1/2. Meanwhile, blockade of ERK1/2 signaling with a specific MEK/ERK1/2 inhibitor U0126 strongly prevented TGFβ2-induced the downregulation of P-cadherin, and the upregulation of α-SMA, collagen type IV, N-cadherin and fibronectin in RPE cells. In addition, we also identified that blockade of ERK1/2 signaling could inhibit not only the canonical TGFβ/Smad signaling, but also the Jagged/Notch pathway. Finally, we found that blockade of Notch pathway with a specific inhibitor DAPT could inhibit TGFβ2-induced the activation of ERK1/2 pathway conversely. Therefore, our study provides evidence that ERK1/2 signaling can cross-interact with the canonical TGFβ/Smad and the Jagged/Notch signaling pathways in RPE cells EMT. ERK1/2 inhibitor may have therapeutic value in the prevention and treatment of PVR and other fibrotic diseases.